Islamic Education Policy: New Directions of ‎Learning Based on Pancasila Learner Profile ‎at Mambaul Ulum Islamic Junior High School ‎in Ponjanan Timur - Abdul Muin,; Rosyid, Moh Zaiful; Habibur Rahman,; Salman Alfarisi, (TADRIS: Jurnal Pendidikan Islam, 2024)
This research aims to investigate the implementation of the Pancasila-based Student Profile Learning Management at Mambaul Ulum Islamic Junior High School in East Ponjanan as a systematic effort to strengthen the character and values of Pancasila among its students. The research method employed a qualitative approach conducted through in-depth interviews, participatory observation, and document analysis. The data were carefully analyzed through the stages of reduction, display, and verification to identify patterns and learning practices as well as the implementation of Islamic education policies and Pancasila values at the school. The results of the research indicate that the implementation of the Pancasila-based Student Profile Learning Management at Mambaul Ulum Islamic Junior High School in East Ponjanan is carried out to strengthen students' character through Pancasila values. The initial step involves teachers as facilitators in understanding these values. Pancasila integration is carried out in the curriculum and extracurricular activities. The roles of parents, teachers, and the community are important in student development. Pancasila values are integrated into both the curriculum and extracurricular activities. Meanwhile, the school culture is also created as conducive as possible to support the instillation of Pancasila values for students at the school.